Pandemic impact on traffic trends and patterns in the city of Belgrade - Glavić, Draženko; Trpković, Ana; Milenković, Marina; Jevremović, Sreten (Transport, 2023)
The appearance of the COVID-19 virus has caused great changes in all spheres of life. Probably the most visible change is the cities’ lockdown, with the suspension of traffic and transport systems. The capital of the Serbia – Belgrade also went through a complete lockdown, which lasted for almost 2 months (53 days). In that period, nearly all activities were reduced, producing significant losses for the whole economic development, healthcare, food supply chain, transport sector and most importantly public transport system. The behaviour of users in such situations can greatly influence the change in the share of certain modes of transport in the overall modal share. The aim of this article is to examine the influence of the COVID-19 pandemic on the transport mode choice for different trip purposes, as well as the examination of different impact factors, such as gender, age, education level, employment status, income, transport mode used before the pandemic, and average distance travelled, on the change of mode of transport. Data of 1143 users were analysed through a survey, for the area of the city of Belgrade, using the McNemar–Bowker test and binary logistic regression. The results showed that pandemic had a significant impact on the transport mode change for all trip purposes. The key factors influencing the change in the mode of transport are factors related to gender, level of education, income, the type of transport used before the pandemic and the average distance travelled. It is also interesting to note that the results showed a significant number of transfers to individual modes of transport, as well as micromobility vehicles and walking. Therefore, this article provides the necessary help in understanding the transport system user’s behaviour, which can facilitate the choice of adequate measures, modes and activities for decision-makers in these specific situations.